Transnational Viewing, Local Meaning: Analyzing K-Drama Consumption Across Indonesia - Oktavia, Luci Afiani (Communica : Journal of Communication, 2025)
The popularity of Korean dramas (K-Dramas) in Indonesia has grown significantly over the past decade, offering a unique opportunity to examine how global media influences local audiences. This study explores the socio-cultural impact of K-Dramas on Indonesian viewers through a mixed-methods approach, including national survey data, YouTube comment analysis, and regional access patterns. The research investigates preferences for subtitled content, perceptions of gender roles, family values, and beauty standards, as well as the extent of cultural hybridization and expressions of national identity in fan discourse. Findings reveal that a majority of viewers prefer subtitled content, particularly among younger urban populations, due to its role in enhancing cultural understanding. K-Dramas shape perceptions of gender and family, reinforcing certain norms while also offering aspirational representations. Beauty ideals presented in these dramas influence consumer behavior and identity formation, though audiences often engage critically with these portrayals. Additionally, the study uncovers a strong presence of cultural hybridization and identity negotiation, alongside regional disparities in media access and digital infrastructure. These insights contribute to our understanding of media globalization, demonstrating how transnational content is both consumed and contested within local contexts. The study highlights the need for inclusive digital policies and further research on the long-term implications of cross-cultural media exposure.